Perancangan Sistem Jurnal Online Berbasis Android di Perpustakaan - Gunaidi, Aang; Yoanda, Sely (UIN Raden Intan Lampung, 2021)
The development of information technology allows the development of an innovative library service system, one of which is the development of a journal management system. Research purposes to develop an android-based online journal system in library. The research method uses a prototype system development method with five stages. The results of this study succeeded in developing an android-based online journal system with several search, submit and review journal features. The results of the system testing show that the web design is attractive to users with a score of 4.0; realibility is good enough to get a mean of 3.0; (c) Responsiness is quite good with a score of 3.0; security 3.0 the system's ability to maintain user data security is good enough; Functionality is quite good with 3.0; Attractivess is very interested in the 5.0 score; Personalization 3.0, this shows that the availability of information to ask questions is good enough.